A touch too much [intrabody communications]. - Goldstein, H.
This paper describes a novel networking technology, called RedTacton, developed by NTT. RedTacton could ultimately let people transfer data to each other's handhelds by means of a handshake or a slap on the back. Using a transmitter embedded in, say, a PDA, RedTacton sends a 5-volt pulse along the surface of the body. The human body shunts most of this electricity to the ground, resulting in a weak electric field that can be modulated to carry signals. The receiver is located either on another part of the body - a component of a hands-free headset or in an acquaintance's PDA. As it senses modulations in the electric field, the receiver decodes them to recover the data. While a good idea, RedTacton unfortunately has no compelling applications that aren't already available. It doesn't work reliably yet and has also been experiencing face perception problems among the general public.
Keywords: NTT Microsystems Integration Laboratories; RedTacton; Data recovery; Data transfer; Electric field; Hands-free headset; Networking technology